Industrial waste residue high-entropy doped positive electrode material and preparation method and application thereof

By high-entropy doping trace elements in industrial waste slag, high-entropy doping cathode materials for lithium-ion battery cathode materials were prepared, which solved the problems of insufficient cyclic performance of high-nickel cathode materials and high dopant costs, and achieved improvement of electrochemical performance and cycle stability and cost reduction.

CN119750581AActive Publication Date: 2025-04-04KUNMING UNIV OF SCI & TECH

Patent Information

Application Number
CN202411945001.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing high-nickel ternary cathode materials have shortcomings in terms of circulation and stability properties, and the commonly used dopants are costly and difficult to obtain.

Method used

By high-entropy doping several trace elements in the industrial waste slag, a high-entropy doped cathode material for industrial waste slag is prepared, which is used as a dopant for the cathode material of lithium-ion batteries, and the mass fraction of silicon in the waste slag is adjusted to improve electrochemical performance and cyclic stability.

Benefits of technology

The electrochemical performance and cyclic stability of the cathode material of lithium-ion batteries is significantly improved, while reducing the cost of dopants, providing a zero-cost high-entropy dopant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750581A_ABST
    Figure CN119750581A_ABST
Patent Text Reader

Abstract

The invention discloses an industrial waste residue high-entropy doped positive electrode material and a preparation method and application thereof, and belongs to the technical field of lithium ion battery positive electrode materials. The preparation method of the industrial waste residue high-entropy doped positive electrode material comprises the following steps: mixing industrial waste residues, a ternary positive electrode material precursor and a lithium source, and performing two-stage roasting to obtain the industrial waste residue high-entropy doped positive electrode material, when the mass fraction of silicon in the industrial waste residues is larger than or equal to 10%, the industrial waste residues are pretreated; the pretreatment comprises the step of carrying out alkali roasting on the industrial waste residues. The mass fraction of silicon in the industrial waste residues is adjusted, the industrial waste residues serve as the doping agent of the positive electrode material of the lithium ion battery, a new thought is provided for the recycling direction of the industrial waste residues and improvement of the cycling stability of the positive electrode material, and the cycling stability of the positive electrode material can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery positive electrode materials, and more specifically relates to an industrial waste slag high entropy doped positive electrode material and a preparation method and application thereof. Background Art

[0002] High-nickel ternary positive electrode materials have gradually become the most important positive electrode materials in the field of new energy electric vehicle power batteries due to their high energy density and low cost. However, with the increase of nickel content, the discharge capacity of high-nickel positive electrode materials increases, and they also have poor cycle performance and stability. Therefore, it is necessary to further optimize the microstructure, component distribution and surface stability of high-nickel positive electrode materials so that the capacity density of lithium-ion batteries can be improved. Among them, due to the advantages of simple and efficient element doping, no additional operating steps and equipment are required, it has become a research hotspot for improving battery stability. At present, the commonly used dopants for lithium-ion battery positive electrode materials include silicon, lithium cobalt oxide, fluoride, sulfide, selenide, etc. Although these dopants can improve the cycle stability of lithium-ion batteries, they have defects such as high price and difficulty in obtaining. Therefore, it is of great significance to develop dopants for lithium-ion battery positive electrode materials with low cost, easy acquisition, and simple processing methods. Summary of the invention

[0003] The purpose of the present invention is to provide an industrial waste slag high entropy doped positive electrode material and a preparation method and application thereof. By high entropy doping of several trace elements in the industrial waste slag, the positive electrode material has good electrochemical properties and cycle stability, so as to solve the problems existing in the above-mentioned prior art and significantly reduce the cost of the dopant used in the positive electrode material of the lithium ion battery on the basis of improving the cycle stability of the lithium ion battery.

[0004] To achieve the above object, the present invention provides the following solutions:

[0005] One of the technical solutions of the present invention is to provide a method for preparing a positive electrode material doped with high entropy from industrial waste residue, comprising the following steps:

[0006] Industrial waste slag, a ternary cathode material precursor and a lithium source are mixed and then calcined in two stages to obtain an industrial waste slag high entropy doped cathode material;

[0007] When the mass fraction of silicon in the industrial waste slag is ≥10%, the method further comprises pre-treating the industrial waste slag; the pre-treatment comprises: alkali roasting the industrial waste slag.

[0008] The present invention adjusts the mass fraction of silicon in industrial waste slag to ensure that the viscosity of the waste slag is reduced and the electrochemical performance is not reduced due to excessive silicon doping. It is used as a dopant for the positive electrode material of lithium ion batteries to improve Li +The diffusion mobility of ions can significantly prevent the occurrence of adverse side reactions, reduce the generation of many adverse byproducts, and significantly improve the electrochemical performance and cycle stability of lithium-ion battery positive electrode materials. When the silicon content in the waste slag is higher than 10%, due to the high viscosity of the waste slag, agglomeration will occur after sintering, which will reduce the battery capacity. Therefore, it is necessary to reduce the silicon content in the waste slag to below 10% through pretreatment.

[0009] Optionally, the industrial waste slag includes one or more of high-magnesium silicon-nickel slag, steel slag, copper slag, zinc slag, lead slag, steel slag and blast furnace slag; the lithium source includes one or more of lithium hydroxide, lithium carbonate, lithium formate and lithium silicate; the chemical formula of the ternary positive electrode material precursor is Ni x1 Co y1 Mn z1 (OH) 2 、Ni x2 Mn y2 Al z2 (OH) 2 or Ni x3 Co y3 Al z3 (OH) 2 , where the value ranges of x1, x2 and x3 are independently 0.8 to 0.95, x1+y1+z1=1, x2+y2+z2=1, x3+y3+z3=1, and y1, z1, y2, z2, y3 and z3 are all not 0.

[0010] Preferably, the molar ratio of the ternary cathode material precursor to the lithium source is 1:1.01-1.05; the mass of the industrial waste slag is 0.5-3% of the mass of the ternary cathode material precursor.

[0011] Preferably, oxygen is introduced during the two-stage calcination process, and the oxygen gas flow rate is 60 to 250 sccm; the parameters of the two-stage calcination are set as follows: the heating rate is independently 3 to 5°C / min, the temperature of the first stage calcination is 400 to 500°C, the insulation time of the first stage calcination is 2 to 5h, the temperature of the second stage calcination is 600 to 800°C, and the insulation time of the second stage calcination is 12 to 15h.

[0012] Optionally, the reagent used for the alkali roasting includes sodium hydroxide.

[0013] Preferably, the alkali roasting temperature is 200-900° C., and the alkali roasting time is 10-60 min.

[0014] Preferably, the pretreatment further comprises washing and drying the product obtained by alkali roasting in sequence.

[0015] Furthermore, the washing includes: dissolving the product obtained by alkali roasting first and then filtering and washing in sequence; the dissolving temperature is 60-80°C, and the dissolving time is 30-40 minutes; the solid-liquid ratio of the dissolving is 9-11:1; the drying temperature is 100-150°C, and the drying time is 600-650 minutes.

[0016] Preferably, the amount of reagent used for the alkali roasting is such that the mass fraction of silicon in the pretreated industrial waste slag is less than 10%; this can not only reduce the viscosity of the industrial waste slag, but also ensure that the electrochemical performance of the obtained positive electrode material will not be reduced due to excessive silicon content during the subsequent doping process.

[0017] The second technical solution of the present invention: provides the industrial waste slag high entropy doped positive electrode material prepared by the preparation method of the industrial waste slag high entropy doped positive electrode material.

[0018] The third technical solution of the present invention is to provide the application of the industrial waste slag high entropy doped positive electrode material in the preparation of lithium ion batteries.

[0019] The fourth technical solution of the present invention is to provide a lithium-ion battery, wherein the positive electrode material of the lithium-ion battery is the industrial waste slag high-entropy doped positive electrode material.

[0020] The present invention discloses the following technical effects:

[0021] 1. The present invention provides a new type of high-entropy dopant at zero cost. It only needs to adjust the mass fraction of silicon in industrial waste slag to use it as a dopant for positive electrode materials of lithium-ion batteries, which provides a new idea for the recycling direction of industrial waste slag and the improvement of the cycle stability of positive electrode materials.

[0022] 2. When the test voltage range of the industrial waste residue high entropy doped positive electrode material of the present invention is 2.8-4.5V, the industrial waste residue high entropy doped positive electrode material has a capacity retention rate of 95.12% after 100 cycles at 1C. The present invention can significantly improve the cycle stability of the positive electrode material by adding industrial waste residue to the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic diagram of the preparation process of the industrial waste slag high entropy doped positive electrode material of the present invention;

[0024] Figure 2 XRD patterns (a) and enlarged portions of the (003) plane of the positive electrode materials obtained in Example 1 and Comparative Example 1 (b);

[0025] Figure 3 The SEM images of the positive electrode materials obtained in Example 1 and Comparative Example 1 are shown in FIG. 1 , wherein a is Example 1 and b is Comparative Example 1;

[0026] Figure 4 This is the EDS image of the positive electrode material obtained in Example 1;

[0027] Figure 5 The cycle performance diagram of the positive electrode materials obtained in Example 1 and Comparative Example 1 at a voltage range of 2.8 to 4.3 V and a rate of 1C;

[0028] Figure 6 XRD patterns (a) and enlarged portions of the (003) plane of the positive electrode materials obtained in Example 2 and Comparative Example 2 (b);

[0029] Figure 7 The graph is a cycle performance diagram of the positive electrode materials obtained in Example 2 and Comparative Example 2 at a voltage range of 2.8 to 4.5 V and a 1C rate.

[0030] Figure 8 XRD patterns (a) and enlarged portions of the (003) plane of the positive electrode materials obtained in Example 3 and Comparative Example 3 (b);

[0031] Fig. 9 The cycle performance diagram of the positive electrode materials obtained in Example 3 and Comparative Example 3 at a voltage range of 2.8 to 4.3 V and a rate of 1C;

[0032] Fig.10 XRD patterns (a) and enlarged portions of the (003) plane of the positive electrode materials obtained in Example 1 and Comparative Example 4 (b);

[0033] Fig.11 The SEM images of impurities in the positive electrode material obtained in Comparative Example 4 at different magnifications;

[0034] Fig.12 This is a cycle performance diagram of the positive electrode material obtained in Comparative Example 4 at a voltage range of 2.8 to 4.3 V and a rate of 1C;

[0035] Fig.13 This is a cycle performance diagram of the positive electrode material obtained in Comparative Example 5 at a voltage range of 2.8 to 4.3 V and a 1C rate. DETAILED DESCRIPTION

[0036] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0037] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0038] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0039] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0040] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0041] The present invention first describes the raw materials used in the embodiments and comparative examples:

[0042] The high-magnesium silicon-nickel slag was taken from a nickel-iron alloy smelter in Yunnan Province. The element composition and content of the high-magnesium silicon-nickel slag are shown in Table 1; the steel slag was taken from a steel mill in Anhui Province. The element composition and content of the steel slag are shown in Table 2;

[0043] Table 1 Element composition and content of high magnesium silicon nickel slag

[0044]

[0045] Table 2 Element composition and content of steel slag

[0046] ω(wt%) Mg Al Si Ca Fe O Other impurities Steel slag 4.76 5.23 4.5 28 21.3 35 1.21

[0047] Ni 0.83 Co 0.12 Mn 0.05 OH 2 and Ni 0.85 Mn 0.09 Al 0.06OH 2 If not specifically limited, it can be prepared according to conventional preparation methods in the art, specifically involving a sol-gel method and a coprecipitation method.

[0048] Example 1

[0049] This embodiment provides a high-magnesium-silicon-nickel slag high entropy doped Ni 0.83 Co 0.12 Mn 0.05 The preparation steps of positive electrode material are as follows:

[0050] (1) mixing high magnesium silicon nickel slag (mass fraction of Si is 19.54%>10%) and sodium hydroxide at a mass ratio of 2.5:1 and grinding them, then calcining them in a muffle furnace at 500° C. for 40 min, and dissolving the solid product in ultrapure water at 70° C. for 30 min at a liquid-solid ratio of 10:1 after cooling, filtering and washing with ultrapure water, and drying at 100° C. for 600 min, thereby reducing the mass fraction of silicon in the high magnesium silicon nickel slag to less than 10%;

[0051] (2) The high magnesium silicon nickel slag (mass Ni 0.83 Co 0.12 Mn 0.05 OH 2 1% by mass), LiOH·H 2 O(LiOH·H 2 O and Ni 0.83 Co 0.12 Mn 0.05 OH 2 The molar ratio is 1.05:1) and Ni 0.83 Co 0.12 Mn 0.05 OH 2 The mixture was placed in a tube furnace and calcined in two stages with oxygen. The oxygen gas flow rate was 200 sccm, the heating rate was 3°C / min, the first stage calcination temperature was 500°C, the holding time was 5h, and the second stage calcination temperature was 750°C, the holding time was 15h. Finally, high-Mg-Si-Ni slag with high entropy doping of Ni was obtained. 0.83 Co 0.12 Mn 0.05 Positive electrode material.

[0052] Example 2

[0053] This embodiment provides a high-magnesium-silicon-nickel slag high entropy doped Ni 0.85 Mn 0.09 Al 0.06 The preparation steps of positive electrode material are as follows:

[0054] (1) mixing high magnesium silicon nickel slag (mass fraction of Si is 19.54%>10%) and sodium hydroxide at a mass ratio of 2.5:1 and grinding them, then calcining them in a muffle furnace at 500° C. for 40 min, and dissolving the solid product in ultrapure water at 70° C. for 30 min at a liquid-solid ratio of 10:1 after cooling, filtering and washing with ultrapure water, and drying at 100° C. for 600 min, thereby reducing the mass fraction of silicon in the high magnesium silicon nickel slag to less than 10%;

[0055] (2) The high magnesium silicon nickel slag (mass Ni 0.85 Mn 0.09 Al 0.06 OH 2 1% by mass), LiOH·H 2 O(LiOH·H 2 O and Ni 0.85 Mn 0.09 Al 0.06 OH 2 The molar ratio is 1.03:1) and Ni 0.83 Co 0.12 Mn 0.05 OH 2 The mixture was placed in a tube furnace and calcined in two stages with oxygen. The oxygen gas flow rate was 200 sccm, the heating rate was 3°C / min, the first stage calcination temperature was 400°C, the holding time was 5h, and the second stage calcination temperature was 750°C, the holding time was 12h. Finally, high-Mg-Si-Ni slag with high entropy doping of Ni was obtained. 0.85 Mn 0.09 Al 0.06 Positive electrode material.

[0056] Example 3

[0057] This embodiment provides a steel slag high entropy doped Ni 0.83 Co 0.12 Mn 0.05 The preparation steps of positive electrode material are as follows:

[0058] Steel slag (mass fraction of Si is 4.5%<10%) (mass fraction of Ni 0.83 Co 0.12 Mn 0.05 OH 2 1% by mass), LiOH·H 2 O(LiOH·H 2 O and Ni 0.83 Co 0.12 Mn 0.05 OH 2 The molar ratio is 1.05:1) and Ni 0.83 Co 0.12 Mn 0.05 OH2 The mixture was placed in a tube furnace and calcined in two stages with oxygen. The oxygen gas flow rate was 200 sccm, the heating rate was 3°C / min, the first stage calcination temperature was 500°C, the holding time was 5h, and the second stage calcination temperature was 750°C, the holding time was 15h. Finally, steel slag high entropy doped Ni was obtained. 0.83 Co 0.12 Mn 0.05 Positive electrode material.

[0059] Comparative Example 1

[0060] The difference from Example 1 is that the addition of high-magnesium silicon-nickel slag is omitted, and the rest is the same as Example 1.

[0061] Figure 2 The XRD patterns of the positive electrode materials obtained in Example 1 and Comparative Example 1; Figure 3 The SEM images of the positive electrode materials obtained in Example 1 and Comparative Example 1 are shown in FIG. 1 , wherein a is Example 1 and b is Comparative Example 1; Figure 4 This is the EDS image of the positive electrode material obtained in Example 1. Figure 2 It can be seen that the diffraction peak of the high entropy doped sample moves to a lower angle compared with the undoped sample, indicating that the bulk doping is successful; Figure 3 It can be seen that the high-Mg-Si-Ni slag prepared in Example 1 is high-entropy doped with Ni 0.83 Co 0.12 Mn 0.05 The spherical structure of the positive electrode material has not changed; Figure 4 It can be seen that the trace elements in high-Mg-Si-Ni slag are evenly distributed in the particles, indicating that the doping is highly uniform.

[0062] Comparative Example 2

[0063] The difference from Example 2 is that the addition of high-magnesium silicon-nickel slag is omitted, and the rest is the same as Example 2.

[0064] Figure 6 The XRD patterns of the positive electrode materials obtained in Example 2 and Comparative Example 2 are shown in FIG. Figure 6 It can be seen that the diffraction peak of the high-entropy doped sample shifts to a lower angle compared to the undoped sample, indicating that the bulk doping is successful.

[0065] Comparative Example 3

[0066] The difference from Example 3 is that the addition of steel slag is omitted, and the rest is the same as Example 3.

[0067] Figure 8 The XRD patterns of the positive electrode materials obtained in Example 3 and Comparative Example 3 are shown in FIG. Figure 8 It can be seen that the diffraction peak of the high-entropy doped sample shifts to a lower angle compared to the undoped sample, indicating that the bulk doping is successful.

[0068] Comparative Example 4

[0069] The difference from Example 1 is that step (1) is omitted, and the positive electrode material is directly prepared using high-magnesium silicon-nickel slag (the mass fraction of Si is 19.54%>10%), and the rest is the same as Example 1.

[0070] Fig.10 XRD patterns (a) and enlarged portions of the (003) plane of the positive electrode materials obtained in Example 1 and Comparative Example 4 (b); Fig.11 The following are SEM images of impurities in the positive electrode material obtained in Comparative Example 4 at different magnifications. Fig.10 and Fig.11 It can be seen that the diffraction peak of the high entropy doped sample moves to a lower angle compared with the undoped sample, indicating that the bulk doping is successful. Fig.11 It can be seen that due to the high silicon content in high-magnesium silicon-nickel slag and the high viscosity of industrial waste slag, trace elements are not fully incorporated during the sintering process, resulting in agglomeration.

[0071] Comparative Example 5

[0072] The difference from Example 1 is that step (1) is omitted, and the "high magnesium silicon nickel slag" is replaced by an equal amount of a commonly used dopant "TiO 2 ", and the rest is the same as in Example 1.

[0073] Performance testing:

[0074] The positive electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 5 were used as positive electrodes, lithium sheets as negative electrodes, and LB002 as electrolytes to assemble lithium ion batteries. The obtained batteries were tested for cycle performance at a voltage range of 2.8 to 4.3 V and a rate of 1C. The results are shown in FIG. Figure 5 , Figure 7 , Fig. 9 , Fig.12 , Fig.13 And as shown in Table 3.

[0075] Table 3 Cyclic stability of lithium-ion batteries prepared from the positive electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 5

[0076]

[0077] Figure 5 The cycle performance diagram of the positive electrode materials obtained in Example 1 and Comparative Example 1 at a voltage range of 2.8 to 4.3 V and a 1C rate. Figure 5 As shown in Table 3, the 100-cycle capacity retention rate of the positive electrode material of Example 1 doped with industrial waste slag is 95.12%, which is significantly improved compared with 78.70% of Comparative Example 1 not doped with industrial waste slag.

[0078] Figure 7 The cycle performance diagram of the positive electrode materials obtained in Example 2 and Comparative Example 2 at a voltage range of 2.8 to 4.5 V and a rate of 1C. Figure 7 As shown in Table 3, the 100-cycle capacity retention rate of the positive electrode material of Example 2 doped with industrial waste slag is 86.46%, which is significantly improved compared with 73.69% of Comparative Example 1 not doped with industrial waste slag.

[0079] Fig. 9 The following is a graph showing the cycle performance of the positive electrode materials obtained in Example 3 and Comparative Example 3 at a voltage range of 2.8 to 4.3 V and a rate of 1C. Fig. 9 As shown in Table 3, the 100-cycle capacity retention rate of the positive electrode material of Example 3 doped with industrial waste slag is 92.29%, which is significantly improved compared with 77.02% of Comparative Example 1 not doped with industrial waste slag.

[0080] Fig.12 The figure is a cycle performance diagram of the positive electrode material obtained in Comparative Example 4 at a voltage range of 2.8 to 4.3 V and a rate of 1C. Fig.12 As shown in Table 3, due to the agglomeration phenomenon in Comparative Example 4, the first cycle discharge capacity of the obtained positive electrode material is reduced.

[0081] Fig.13 The figure is a cycle performance diagram of the positive electrode material obtained in Comparative Example 5 at a voltage range of 2.8 to 4.3 V and a rate of 1C. Fig.13 As shown in Table 3, the positive electrode material of Example 1 doped with industrial waste slag and the positive electrode material doped with TiO 2 Compared with the positive electrode material described in Comparative Example 5, the 100-cycle capacity retention rate is improved, and the dopant used is solid waste, which has lower cost and is easier to obtain.

[0082] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0083] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a positive electrode material doped with high entropy from industrial waste residue, characterized in that: The steps include: Industrial waste slag, a ternary cathode material precursor and a lithium source are mixed and then calcined in two stages to obtain an industrial waste slag high entropy doped cathode material; When the mass fraction of silicon in the industrial waste slag is ≥10%, the method further comprises pre-treating the industrial waste slag; the pre-treatment comprises: alkali roasting the industrial waste slag.

2. The preparation method according to claim 1, characterized in that: The industrial waste slag includes one or more of high-magnesium-silicon-nickel slag, copper slag, zinc slag, lead slag, steel slag and blast furnace slag; and / or, the lithium source includes one or more of lithium hydroxide, lithium carbonate, lithium formate and lithium silicate; and / or, the chemical formula of the ternary positive electrode material precursor is Ni x1 Co y1 Mn z1 (OH)2、Ni x2 Mn y2 Al z2 (OH)2 or Ni x3 Co y3 Al z3 (OH)2, wherein the value ranges of x1, x2 and x3 are independently 0.8-0.95, x1+y1+z1=1, x2+y2+z2=1, x3+y3+z3=1, and y1, z1, y2, z2, y3 and z3 are not 0.

3. The preparation method according to claim 1, characterized in that: The molar ratio of the ternary positive electrode material precursor to the lithium source is 1:1.01-1.05; the mass of the industrial waste slag is 0.5-3% of the mass of the ternary positive electrode material precursor.

4. The preparation method according to claim 1, characterized in that: During the two-stage calcination process, oxygen is introduced, and the oxygen gas flow rate is 60 to 250 sccm; the parameters of the two-stage calcination are set as follows: the heating rate is independently 3 to 5°C / min, the temperature of the first stage calcination is 400 to 500°C, the insulation time of the first stage calcination is 2 to 5h, the temperature of the second stage calcination is 600 to 800°C, and the insulation time of the second stage calcination is 12 to 15h.

5. The preparation method according to claim 1, characterized in that: The reagent used for the alkali roasting includes sodium hydroxide; the temperature of the alkali roasting is 200-900° C., and the time of the alkali roasting is 10-60 minutes.

6. The preparation method according to claim 1, characterized in that: The pretreatment further comprises washing and drying the product obtained by alkali roasting in sequence.

7. The preparation method according to claim 6, characterized in that: The amount of the reagent used for the alkali roasting is such that the mass fraction of silicon in the pretreated industrial waste slag is less than 10%.

8. The industrial waste slag high entropy doped positive electrode material prepared by the method for preparing the industrial waste slag high entropy doped positive electrode material according to any one of claims 1 to 7.

9. Use of the industrial waste slag high entropy doped positive electrode material according to claim 8 in the preparation of lithium ion batteries.

10. A lithium ion battery, characterized in that: The positive electrode material of the lithium-ion battery is the industrial waste slag high-entropy doped positive electrode material as described in claim 8.

Citation Information

Patent Citations

  • Method for preparing multi-component doped lithium ferrous phosphate by utilizing high phosphorus slag

    CN101898757A

  • Method for preparing monocrystal-like ternary positive electrode material by regenerating waste lithium ion battery positive electrode material

    CN113328161A

  • Method for preparing ternary positive electrode material by using waste residue containing manganese, cobalt and nickel

    CN113611857A

  • High-low-valence element synergistically doped high-nickel ternary positive electrode material, preparation method thereof and application of high-low-valence element synergistically doped high-nickel ternary positive electrode material in high-voltage lithium ion battery

    CN118173778A

  • Doped ternary precursor, positive electrode material, and preparation method

    WO2022237576A1

Cited By

  • High-entropy doped direct regenerative battery positive electrode material as well as preparation method and application thereof

    CN120300164A